Hierarchon vol. 2: a dictionary of AHP hierarchies - Saaty, Thomas; Islam, Rafikul (RWS Publications, 2015)
Researchers have been continually developing ways and means to improve quality in decision making. The success of a methodology is judged by its acceptability by the decision makers. In this context, it is beyond any argument that AHP has been massively successful. Readers of this volume will see, once again, that AHP has been applied in widely diverse areas. However, there are many more applications of AHP in other areas that are not reported here. We also don’t claim that the set of applications of AHP in the reported areas is exhaustive; it is far from complete. In fact, it will not be possible to capture all the real-world applications of AHP even by publishing many volumes of this kind. We hope that the readers will find the present compilation useful.